Expression profiles of lncRNAs and their possible regulatory role in monocrotaline-induced HSOS in rats - Ismail, Mohammed; Zhang, Xi; Taha, Reham; Elhafiz, Muhanad; Zhang, Qianwen; Yousef, Bashir A.; Huang, Xin; Jiang, Zhenzhou; Zhang, Luyong; Sun, Lixin (Frontiers in Genetics, 2023)
Aims: Long non-coding RNAs (lncRNAs) contribute to the regulation of vital physiological processes and play a role in the pathogenesis of many diseases. Monocrotaline (MCT) can cause large-scale outbreaks of toxic liver disease in humans and animals in the form of hepatic sinusoidal obstruction syndrome (HSOS). Although many experiments have been carried out to explain the pathogenesis of Monocrotaline-induced hepatic sinusoidal obstruction syndrome and to develop treatments for it, no studies have examined the role of Long non-coding RNAs in this condition. This study aimed to investigate the Long non-coding RNAs–mRNA regulation network in Monocrotaline-induced hepatic sinusoidal obstruction syndrome in rats. Main methods: We established a model for MCT-induced hepatic sinusoidal obstruction syndrome, and then carried out microarray for liver tissues of SD rats in a model of early hepatic sinusoidal obstruction syndrome (12 h Monocrotaline treatment vs. control group) to investigate the differentially expressed Long non-coding RNAs and mRNAs in early hepatotoxicity. This was followed by RT-PCR analysis of selected Long non-coding RNAs, which were markedly altered. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genome analyses were also conducted. Key findings: 176 Long non-coding RNAs (63 downregulated and 113 upregulated) and 4,221 mRNAs (2,385 downregulated and 1836 upregulated) were differentially expressed in the Monocrotaline-treated group compared to the control group. The biological processes identified in GO enrichment analysis as playing a role in hepatotoxicity were positive regulation of guanosine triphosphate phosphohydrolase, liver development, and the oxidation-reduction process. Pathway analysis revealed that the metabolism pathways, gap junction, and ribosome biogenesis in eukaryotes were closely related to Monocrotaline-induced hepatotoxicity. According to these analyses, LOC102552718 might play an essential role in hepatotoxicity mechanisms by regulating the expression of inositol 1,4,5-trisphosphate receptor-1 (Itpr-1). Significance: This study provides a basis for further research on the molecular mechanisms underlying Monocrotaline-induced hepatotoxicity and its treatment, especially in the early stage, when successful treatment is critical before irreversible liver damage occurs.